Benchmarking for accountability on obesity prevention: evaluation of the Healthy Food Environment Policy Index (Food-EPI) in Australia (2016–2020). Issue 2 (28th February 2022) - Kwon, Janelle; Reeve, Erica; Mann, Davina; Swinburn, Boyd; Sacks, Gary
Abstract: Objective: Despite broad agreement on the need for comprehensive policy action to improve the healthiness of food environments, implementation of recommended policies has been slow and fragmented. Benchmarking is increasingly being used to strengthen accountability for action. However, there have been few evaluations of benchmarking and accountability initiatives to understand their contribution to policy change. This study aimed to evaluate the impact of the Healthy Food Environment Policy Index (Food-EPI) Australia initiative (2016–2020) that assessed Australian governments on their progress in implementing recommended policies for improving food environments. Design: A convergent mixed methods approach was employed incorporating data from online surveys (conducted in 2017 and 2020) and in-depth semi-structured interviews (conducted in 2020). Data were analysed against a pre-defined logic model. Setting: Australia. Participants: Interviews: twenty stakeholders (sixteen government, four non-government). Online surveys: fifty-three non-government stakeholders (52 % response rate) in 2017; thirty-four non-government stakeholders (36 % response rate) in 2020. Results: The Food-EPI process involved extensive engagement with government officials and the broader public health community across Australia. Food-EPI Australia was found to support policy processes, including as a tool to increase knowledge of good practice, as a process for collaboration and as an authoritative reference to support policy decisions and advocacy strategies. Conclusions: Key stakeholders involved in the Food-EPI Australia process viewed it as a valuable initiative that should be repeated to maximise its value as an accountability mechanism. The highly collaborative nature of the initiative was seen as a key strength that could inform design of other benchmarking processes.